ARABIC PROGRAM MANAGEMENT IN MODERN ISLAMIC BOARDING SCHOOL: A COMPARATIVE CASE STUDY - Della Ayu Syafira; Maskuri Maskuri; Muhammad Jundi; Suleman D. Kadir (Tarbiyah Faculty of Ibrahimy University Ibrahimy University, Situbondo, Indonesia, 2025)
The increasing demand for Arabic proficiency among students in Islamic boarding schools highlights the need to investigate the management of Arabic language programs to ensure effective learning outcomes. This study addresses the importance of investigating the management of Arabic language programs in Islamic boarding schools. Specifically, it focuses on Mambaus Sholihin and Al-Falah, renowned pesantrens with exceptional Arabic language programs in their respective regions. By comparing the planning, implementation, and evaluation aspects of these programs, valuable insights can be derived both internally and externally. Using a qualitative descriptive approach, this research employs a comparative case study design, utilizing data collection methods such as observation and interviews. The data is analyzed through transcription, data reduction, and integration of interview and observation data. The reasearch finds: 1) Planning: The program is systematically designed in both institutions. There are variations in the forms of learning activities between the two institutions, but the learning objectives are the same. The selection process for tutors differs between the pesantrens. 2) Implementation: The program is implemented using direct and drill methods in both institutions. Although the learning materials differ, they are aligned with the curriculum of Pondok Modern Gontor. The use of electronic media in learning is limited and infrequent. 3) Evaluation: The evaluation of both program and learning in both institutions is lacking structured and systematic approaches, resulting in a lack of measurable progress in learning. The planning and implementation of Arabic language programs at Al-Falah are more responsive to student needs compared to Mambaus Sholihin. However, both institutions lack optimal evaluation and rely on subjective observations, highlighting the need for objective evaluation methods.